A Customer Relationship Management (CRM) Aprroach with the Spiral Model (Case Study: Information System at Optik Sejahtera) - Fransisca, Diandra Chika; Linri, Spanica Pamfilia (ExcelingTech, 2020)
Optik Sejahtera is a company engaged in the sale of eye sight/ vision aids or often called glasses. In addition to glasses made of stainless and fiber, there are also many manufacturers in Indonesia that produce glasses from wood. The marketing of wood eyewear products still has problems, among which is still many people do not know about this product. This condition led to stagnant sales transactions in Optik Sejahtera. CRM (Customer Relationship Management) approach method is a marketing activity built on four pillars namely identifying, attracting, maintaining and strengthening brand loyalty, or strengthening relationships to achieve mutually beneficial goal. Therefore, information systems are required with the CRM approach method on Optik Sejahtera to increase sales transactions i.e. with spiral models. Spiral model steps are communication with customers, planning, risk analysis, engineering, construction and launch, and customer evaluation. The systems in this study use the MySQL database. The results of this study based on analysis system of hypothesis test showed before using the system it took 8,6840 minutes and after using the system it only took 4,3197 minutes. It means, there are changes in sales transactions before and after using the information system in Optik Sejahtera. In other words, the information system on Optik Sejahtera could resulted in an increase of sales transactions. In addition, the results of the study in benefit testing obtained a percentage for utilization of 89.98%, effectiveness of 90%, and efficiency of 92.23%. This means that information systems in Optik Sejahtera using CRM approach with spiral models can increase efficiency in sales transactions.